3D Printing of High‐Performance Isocyanate Ester Thermosets. Issue 11 (13th September 2020) - Wu, Tao; Jiang, Pan; Ji, Zhongying; Guo, Yuxiong; Wang, Xiaolong; Zhou, Feng; Liu, Weimin
Abstract: High‐performance materials for 3D printing are increasingly desired to meet more and more requirements from various fields including aerospace and high‐tech equipment. In this study, 3D printing of isocyanate ester thermosets with high performances, such as excellent mechanical properties and thermal resistance, is realized with a facile method. A precursor of acrylate isocyanate ester with good photocuring capability is first synthesized with the reaction of tolylene‐2, 4‐diisocyanate and hydroxypropyl acrylate. Then, mixed with diluent NeoRad U‐6282 and photoinitiator Irgacure 819, it forms ultraviolet curable resins for 3D printing. The digital light processing 3D printing of the resins results in high‐precision 3D structures, which finally turn out high‐performance thermoset materials after the cross‐linking of isocyanate groups at elevated temperature. 3D printing of isocyanate ester thermosets with high printing accuracy, excellent mechanical properties, and good heat resistance will expand the applications of 3D printing by meeting the high demands from many industries on both mechanical and thermal performance. Abstract : 3D printing of thermalsetting isocyanate ester (ICE) is realized with ultraviolet curing forming and then following thermal treatment. The resultants, due to the large number of isocyanurate six‐membered heterocyclic rings formed in the thermal‐curing exhibit excellent mechanical properties and thermal resistance. The 3D printed ICE architectures with high accuracy will find potential applications from automobile to aerospace.